Tell Us What You Really Think: Implementing a Mixed-methods Approach to Library User Assessment - Lidiya Grote; Emily Dill; Jennifer Hardin (Journal of New Librarianship, 2023)
This article presents an analysis of student feedback received via formal biennial survey and informal post-it notes assessment, and advocates for the use of informal assessment methods to supplement formal methodologies. A biennial satisfaction survey and an informal post-it notes assessment were employed to collect data from library users and yielded comprehensive, timely, and actionable feedback from the students, faculty, and staff. Feedback received from the two assessment methods allowed the University Library of Columbus (ULC) to gain a greater understanding of user needs and preferences which was used to improve library spaces, resources, and services to increase user satisfaction. While each method has advantages and disadvantages, combining varied assessment methods helped the ULC to gain a more holistic understanding of its users and provided a rich set of actionable data. Furthermore, student feedback is a valuable tool for library advocacy and outreach to both the university community at large and administrators.